Analytical model of secondary electron emission yield in electron beam irradiated insulators. (September 2018) - Ghorbel, N.; Kallel, A.; Damamme, G.
Highlights: Modeling charge generation, transport and trapping phenomena in insulators. SEE evolution versus trapped charges in the dielectric is modeled. Analysis of secondary electron emission experiments. Drift-diffusion-reaction (DDR) model in plane geometry is used. Prediction of the electron mobility and diffusion coefficient in insulators. Abstract: The study of secondary electron emission (SEE) yield as a function of the kinetic energy of the incident primary electron beam and its evolution with charge accumulation inside insulators is a source of valuable information (even though an indirect one) on charge transport and trapping phenomena. We will show that this evolution is essentially due, in plane geometry conditions (achieved using a defocused electron beam), to the electric field effect (due to the accumulation of trapped charges in the bulk) in the escape zone of secondary electrons and not to modifications of trapping cross sections, which only have side effects. We propose an analytical model including the main basic phenomena underlying the space charge dynamics. It will be observed that such a model makes it possible to reproduce both qualitatively and quantitatively the measurement of SEE evolution as well as to provide helpful indications concerning charge transport (more precisely, the ratios between the mobility and diffusion coefficient with the thermal velocity of the charge carrier).